Hubungan antara Faktor Motivasi dan Supervisi dengan Kinerja Perawat dalam Pendokumentasian Discharge Planning di RSUD Gambiran Kota Kediri - Natasia, Nazvia; Andarini, Sri; Koeswo, Mulyatim (Jurnal Aplikasi Manajemen, 2014)
The aim of this study is to find the corelation between motivation and supervision by looking at nurses'working performance in documentation discharge planning. This study is a quantitative study of correlative quantitative type with cross sectional approach. Motivation and supervision was measured by using questionnaire, all questionnaires used five scales of likert. Discharge planning documentation was measured by using checklist observation. Univariant, bi-variant, and multivariate analyses are used to analyze the relevant data. Bi-variant analysis test indicates that there is a correlation between motivation and supervision with performance at work of nurse in documentation discharge planning. Supervision is corelation more than motivation.